Developments in Technology-Delivered Psychological Interventions (2012)
The worldwide penetration of the Internet and its related technologies, the rapid developments of new technologies and the pervasive use of technology in people’s lives, are indicators that we live in a technological age. New technologies and their potential for use in psychological interventions and mental health services have not gone unnoticed. The last 15 years or so have witnessed the employment of new technologies in developing and delivering a variety of psychological interventions, these include information WebPages, internet-based computer programs that are addressed to treatment of specific problems, the use of mobile phones and games to help psychological practice, among others. However, while a broad range of technology- delivered psychological interventions have demonstrated success in high-income countries, little is known of their potential for countries such as Colombia. The paper begins with a brief history, followed by an overview of the field of technology-delivered psychological interventions. Lastly, the paper seeks to present a justification for the potential use of technology delivered psychological interventions in Colombia.